Perceived Enjoyment, Compatibility dan Social Influence dalam Adopsi Media Sosial - Dyah Sugandini; Mohamad Irhas Effendi; Yuni Istanto; Rahajeng Arundati; Esti Dwi Rahmawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat UPN Veteran Yogyakarta, 2020)
This study is a descriptive study to explain perceived enjoyment, compatibility and social influence in social media setting. This study used 100 respondents who have used social media in their daily lives. This study does not limit respondents in terms of gender or other respondents backgrounds. Data were analyzed from the average respondents answers obtained during the study. The results of this study indicate that the items used to measure perceived enjoyment, compatibility, and social influence show relatively very high answers. This research can be the basis for further research in predicting the adoption of information technology innovations by using variables of perceived enjoyment, compatibility and social influence.